High-Resolution Differential Thermography of Semiconductor Edifices - Sastine, Vera Marie; Cemine, Vernon Julius; Blanca, Carlo Mar; Saloma, Caesar (Science Diliman: A Journal of Pure and Applied Sciences; Vol 16 No 2 (2004), 2007)
We develop a cost-effective, high-resolution, and noninvasive imaging technique for thermal mapping of semiconductor edifices in integrated circuits. Initial implementation was done using a power-stabilized optical feedback laser system that detects changes in the optical beam-induced current when the package temperature of the device is increased. The linear change in detected current can be translated to a thermal gradient, which can reveal semiconductor “hotspots”—localized sites with anomalous thermal activity. These locales are possible fault sites or areas susceptible to defects, which are the best jump-off points for failure analysis.